290 Are Clients Satisfied with Integrated Care? Enhancing Client Feedback on Discharge from a Domiciliary Based Multidisciplinary Integrated Care Service. (16th September 2019) - Boyle, Nichola; McDonnell, Sinead; Balasubramanian, Subha; Reynolds, Niamh; Geary, Niamh; O'Shea, Diarmuid; Hession, Eilis
Abstract: Background: The Integrated Care Programme for Older People has supported the development of integrated care services at pioneer sites in Ireland, each developed to meet local needs. Patient Reported Experience Measures (PREMs have been used to evaluate user experience in intermediate care in the United Kingdom. This project aimed to evaluate client experience of a domiciliary based, multidisciplinary, integrated care service. Methods: A qualitative audit of the experience of clients of the Older Persons' Integrated Care Team (OPICT) was performed. This project was undertaken in conjunction with the Royal College of Physicians of Ireland's Quality Improvement in Action programme. A feedback questionnaire was designed and distributed to consecutively discharged clients from OPICT from February 2019, providing qualitative assessment for service improvement. The results of feedback from the first questionnaire design are reported. Results: Twenty OPICT clients received a feedback questionnaire following their final interaction with the OPICT service. Eighteen clients responded: 11 males and 9 females with mean age 81 years. Two male clients did not return the questionnaire (mean age 86 years). In terms of the treatment and advice provided by the team, all 18 clients agreed with statements that they were involved in decision making, treatment was explained in a way that they could understand and was effective and met their needs. All clients responding indicated that they were listened to, treated with dignity and had confidence and trust in the team. All 18 respondents would recommend the service to another older person. Respondents also provided individual comments which all indicated satisfaction with the service. Conclusion: Older people accessing integrated care delivered in their home reported a positive experience and can provide important information on further service development.